Si(001) c(4×2)–p(2×2) surface phase transitions induced by electric fields and doping - Schmidt, Wolf Gero; Seino, K. (Current Applied Physics)

Ga-richGaAs(001)surface fromab initiocalculations: Atomic structure of the(4×6)and(6×6)reconstructions - Seino, K.; Schmidt, Wolf Gero; Ohtake, A. (Physical Review B)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Semiempirical van der Waals correction to the density functional description of solids and molecular structures - Ortmann, F.; Bechstedt, F.; Schmidt, Wolf Gero (Physical Review B)

Aus dem Englischen ins Italienische: M. Cohen, Wittgestein’s Beetle and Other Thought Experiments

Asmuth, Christoph, Interpretation – Transformation, Vandenhoeck&Ruprecht, Amsterdam - Ficara, Elena (Rivista di Filosofia)

Die Ontologie in der „Kritik der reinen Vernunft“ - Ficara, Elena

Comparison of Performance and Realization Effort of a Very Sparse Matrix Converter to a Voltage DC Link PWM Inverter with Active Front End - Round, Simon; Schafmeister, Frank; Kolar, Johann (IEEJ Transactions of the Institute of Electrical Engineers of Japan)

Transient peak currents in permanent magnet synchronous motors for symmetrical short circuits - Meyer, M.; Böcker, Joachim (International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2006. SPEEDAM 2006.)

Energy Management for an Onboard Storage System Based on Multi-Objective Optimization - Knoke, Tobias; Romaus, Christoph; Böcker, Joachim; Dell'Aere, Alessandro; Witting, Katrin (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Modelling and Control of a Multi-Mass Ultrasonic Motor for Airborne Applications - Wetzel, H.; Fröhleke, N.; Böcker, Joachim; Ouchouche, S.; Bezanere, D.; Cugnon, F. (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Self-Optimization as a Framework for Advanced Control Systems - Böcker, Joachim; Schulz, Bernd; Knoke, Tobias; Fröhleke, Norbert (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Investigation of Power Supplies for a Piezoelectric Brake Actuator in Aircrafts - Li, Rongyuan; Fröhleke, Norbert; Wetzel, Hermann; Böcker, Joachim (2006 CES/IEEE 5th International Power Electronics and Motion Control Conference)

High Efficient 3kW Three-Stage Power Supply - Wetzel, H.; Fröhleke, N.; Böcker, Joachim; Ide, P. (Twenty-First Annual IEEE Applied Power Electronics Conference and Exposition, 2006. APEC '06.)

Advanced convoy control strategy for autonomously driven railway vehicles - Henke, C.; Fröhleke, Norbert; Böcker, Joachim (2006 IEEE Intelligent Transportation Systems Conference)

Drive Control and Position Measurement of RailCab Vehicles Driven by Linear Motors - Pottharst, A.; Henke, C.; Schneider, T.; Böcker, Joachim; Grotstollen, H. (Int. Symposium on Instrumentation and Control Technology (ISICT), Beijing, China)

Redundante Positionserfassung für ein spurgeführtes linearmotorgetriebenes Bahnfahrzeug - Schneider, T.; Schulz, B.; Henke, C.; Böcker, Joachim (Workshop Entwurf mechatronischer Systeme, Heinz-Nixdorf-Institut, Universität Paderborn,)

Optimum Control for Interior Permanent Magnet Synchronous Motors (IPMSM) in Constant Torque and Flux Weakening Range - Meyer, Michael; Böcker, Joachim (2006 12th International Power Electronics and Motion Control Conference)

Psychologism and the Distinction between Discovery and Justification - Peckhaus, Volker (Revisiting Discovery and Justification. Historical and Philosophical Perspectives on the Context Distinction)

Der Baum der Erkenntnis - Peckhaus, Volker (Die besten Nebenrollen. 50 Porträts biblischer Randfiguren)

Predeductive Reasoning - Peckhaus, Volker (Demonstrative and Non-demonstrative Reasoning in Mathematics and Natural Sciences. Workshop University of Rome ‘La Sapienza’, Rome, Villa Mirafiori, 16-17 June 2005)

Die Aktualität der Logik als Organon - Peckhaus, Volker (Kreativität. XX. Deutscher Kongress für Philosophie. 26.–30. September 2005 an der Technischen Universität Berlin. Kolloquiumsbeiträge)

Preface - Peckhaus, Volker; Löwe, Benedikt; Räsch, Thoralf (Foundations of Formal Sciences IV. The History of the Concept of Formal Sciences)

Rankings und Evaluationen im Bildungsbereich. - Lück, Sonja; Kraft, Manfred (Genus oeconomicum. Ökonomie - Macht - Geschlechterverhältnisse)

Husserl, Edmund, "Philosophy of Arithmetik. Psychological and Logical Investigations with Supplementary Texts from 1887-1901", übers. u. hg. v. Dallas Willard, Kluwer: Dordrecht 2003 (Collected Works, Bd. 10) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Copeland, B. Jack, "The Essential Turing. Seminal Writings in Computing, Logic, Philosophy, Artificial Intelligence, and Artificial Life plus ‘The Secrets of Enigma’", Clarendon Press: Oxford 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Briefe an František Príhonský (1824–1948)", 3 Bde., hg. v. Jan Berg (Bernard-Bolzano-Gesamtausgabe, R. III, 3, 1–3), Frommann-Holzboog: Stuttgart-Bad Cannstatt 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Vermischte Mathematische Schriften 1832–1848, Teil 1", hg. v. Jan Berg (Bernard-Bolzano-Gesamtausgabe, R. II.A.11.1), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Cassini, Alejandro, “Newton and Leibniz on Non-substantial Space”, In: Theoria. Segunda Epoca 20, Nr. 52 (2005), 25-42 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Lacki, Jan, “Styles of Physical Thinking Versus Mathematical Ones”, In: Synthese 134 (2003), 273-288 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Burgess, John P., “Mathematics and the Bleak House”, In: Philosophia Mathematics (3) 12 (2004), 18-36 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Burgess, John P, "Fixing Frege", Princeton University Press: Princeton, NJ 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Floyd, Juliet/Shieh, Sanford (Hgg.), "Future Pasts. The Analytic Tradition in Twentieth-Century Philosophy. Dedicated to Burton Dreben", Oxford University Press: Oxford 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Stöltzner, Michael, “On Optimism and Opportunism in Applied Mathematics. Mark Wilson meets John von Neumann on Mathematical Ontology”, In: Erkenntnis 69 (2004), 121–143 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Weigel, Erhard, "Universi corporis pansophici caput summum. Werke I", hg. u. eingel. v. Thomas Behme, Frommann-Holzboog: Stuttgart-Bad Cannstatt 2003 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

van Dalen, Dirk, "Mystic, Geometer, and Intuitionist. The Life of L.E.J. Brouwer, Vol. 2: Hope and Disillusion", Oxford University Press: Oxford 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hoffmann, Sarah, “Kitcher, Ideal Agents, and Fictionalism”, In: Philosophia Mathematica (3) 12 (2004), 3–17 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Weiner, Joan, "Frege Explained. From Arithmetic to Analytic Philosophy", Open Court: Chicago, IL 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gezielt fördern. Verben, Präpositionen, Adverbien, Konjunktionen. Arbeitsheft 5./6 - Breitkopf, Kathleen; Heinz, Hans Joachim; Niederhaus, Constanze; Plieninger, Martin

Martin, Donald A., “Gödel’s Conceptual Realism”, In: Bulletin of Symbolic Logic 11 (2005), 207–224 - Peckhaus, Volker (Mathematical Reviews)

Ehrlich, Philip, “The Rise of non-Archimedean Mathematics and the Roots of a Misconception. I. The Emergence of non-Archimedean Systems of Magnitudes”, In: Archives of the History of Exact Science 60 (2006), 1–121 - Peckhaus, Volker (Mathematical Reviews)

Tapp, Christian, "Kardinalität und Kardinäle. Wissenschaftshistorische Aufarbeitung der Korrespondenz zwischen Georg Cantor und katholischen Theologen seiner Zeit", Steiner: Stuttgart 2005 - Peckhaus, Volker (Mathematical Reviews)

Ewald, William, “Hilbert’s Wide Program”, in: Logic Colloquium 2000, Association for Symbolic Logic: Urbana 2005 (Lect. Notes Logic; 19), 228–251 - Peckhaus, Volker (Mathematical Reviews)

Eder, Ulrike: ,Auf die mehrere Ausbreitung der teutschen Sprache soll fürgedacht werden’: Deutsch als Fremd- und Zweitsprache im Unterrichtssystem der Donaumonarchie zur Regierungszeit Maria Theresias und Josephs II - Ptashnyk, Stefaniya (Studia Linguistica, Heft XXXI/2012. Wroclaw: Wydawnictwo Uniwersytetu Wroclawskiego)

Eder, Ulrike: „Auf die mehrere Ausbreitung der teutschen Sprache soll fürgedacht werden“: Deutsch als Fremd- und Zweitsprache im Unterrichtssystem der Donaumonarchie zur Regierungszeit Maria Theresias und Josephs II - Ptashnyk, Stefaniya (Studia Linguistica XXXI, Wroclaw 2012)

Quasiparticle corrections to the electronic properties of anion vacancies at GaAs(110) and InP(110) - Hedström, Magnus; Schindlmayr, Arno; Schwarz, Günther; Scheffler, Matthias (Physical Review Letters)
We propose a new method for calculating optical defect levels and thermodynamic charge-transition levels of point defects in semiconductors, which includes quasiparticle corrections to the Kohn-Sham eigenvalues of density-functional theory. Its applicability is demonstrated for anion vacancies at the (110) surfaces of III–V semiconductors. We find the (+/0) charge-transition level to be 0.49 eV above the surface valence-band maximum for GaAs(110) and 0.82 eV for InP(110). The results show a clear improvement over the local-density approximation and agree closely with an experimental analysis.

Elimination of the linearization error in GW calculations based on the linearized augmented-plane-wave method - Friedrich, Christoph; Schindlmayr, Arno; Blügel, Stefan; Kotani, Takao (Physical Review B)
This paper investigates the influence of the basis set on the GW self-energy correction in the full-potential linearized augmented-plane-wave (LAPW) approach and similar linearized all-electron methods. A systematic improvement is achieved by including local orbitals that are defined as second and higher energy derivatives of solutions to the radial scalar-relativistic Dirac equation and thus constitute a natural extension of the LAPW basis set. Within this approach linearization errors can be eliminated, and the basis set becomes complete. While the exchange contribution to the self-energy is little affected by the increased basis-set flexibility, the correlation contribution benefits from the better description of the unoccupied states, as do the quasiparticle energies. The resulting band gaps remain relatively unaffected, however; for Si we find an increase of 0.03 eV.

Dynamische Basisontologie und kooperative Semantiken. Möglichkeiten und Grenzen der Kombination begrifflicher und graphischer Wissensorganisation - Hagengruber, Ruth (HNI Jahresbericht)

Dynamic Ontology and Cooperative Semantics. The Combination of Conceptual and Graphical Knowledge Representation: Its Possibilities and Limits - Hagengruber, Ruth (HNI Annual Report)

Das Leseplakat. Eine Aufgabenstellung zur Rezeption vorgelesener Bücher - Kruse, Iris (Selbsttätigkeit und Aufgabenstellungen in der Grundschule. Grundschulunterricht)